Trivializing violence: Marginalized youth narrating everyday violence - Henriksen, Ann-Karina (Theoretical criminology, 2018)
This article analyzes narratives of violence based on interviews with 43 marginalized young Danish people. Their narratives reveal that violence is not only experienced as singular, dramatic encounters; violence is also trivialized in their everyday lives. By drawing on anthropological perspectives on everyday violence, we propose a sensitizing framework that enables the exploration of trivialized violence. This framework integrates three perspectives on the process of trivialization: the accumulation of violence; the embodiment of violence; and the temporal and spatial entanglement of violence. This analysis shows how multiple experiences of violence—as victim, witness, or perpetrator—intersect and mutually inform each other, thereby shaping the everyday lives and dispositions of the marginalized youth. The concept of trivialized violence is a theoretical contribution to cultural and narrative criminology research concerned with the everyday experiences of living with violence.